Health effects of ozone and particulate matter pollution in China: a province-level CGE analysis - Nam, Kyung-Min; Zhang, Xu; Zhong, Min; Saikawa, Eri; Zhang, Xiliang (The Annals of regional science, 2019)
In this study, we estimate the cost of PM 2.5 and O 3 pollution in China and explore how it differs by province. For the analysis, we extend the China Regional Energy Model—a computable general equilibrium model of the Chinese economy—to explicitly represent the pollution-health linkage within a larger economic system. Our results show that health damage from air pollution in China is substantially large. For each year between 2010 and 2030, China’s welfare loss from excess pollution is estimated to be 3.2–5.1% of the baseline level when welfare is measured as the sum of consumption and leisure. The PM 2.5 share of the costs was > 13 times as large as the O 3 share, and premature deaths from chronic exposure to PM 2.5 were the single most important health endpoint, accounting for ≤ 56% of the total costs. Cross-regional heterogeneity is substantial, and populous and wealthy Eastern China is subject to particularly large health damage. When the size of provincial economies is controlled for, however, the dominance of the eastern region is less obvious and several inland provinces (e.g., Henan, Shanxi, and Chongqing) also suffer high pollution-health costs, due to low air quality and fast productivity growth. Finally, broader economic loss from inefficient resource allocation and its cumulative effects, which is often neglected in static analysis, accounts for > 29% of the total costs. Overlooking this cost component will, in particular, lead to substantial underestimation for China’s central and western regions, whose economies are growing fast.